The Perception of Impact of Money in Local Government Election: A Study of Chapainawabganj Sadar - Mst. Sadia Khatun; Mahmud , Dr. Md. Sultan; Arafat, Md. Yeasir; Alam , Md. Mahbubul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Fair and transparent elections, composed of informed citizenry and worthy leaders, are the lifeblood of a democratic system. The study upholds the significant and multifaceted role that money plays in influencing the outcomes of local government elections, with a particular focus on Chapainawabganj Sadar. In recent years, the influence of financial power in democratic processes, especially at the grassroots level, has become increasingly evident. This research aims to understand how monetary involvement affects voter behavior, candidate selection, campaign strategies, and ultimately, election results in the region. Through both quantitative and qualitative methods, including surveys, interviews, and analysis, the study finds that money is a dominant factor in determining electoral success. Candidates with substantial financial resources are able to conduct extensive campaigns, offer incentives to voters, and gain higher visibility through posters, banners, and media coverage. On the other hand, financially weaker candidates often struggle to compete on an equal footing, regardless of their merit or community support. The findings also suggest that voters in Chapainawabganj Sadar are increasingly becoming influenced by short-term material benefits such as cash, gifts, or promises of future favours, which undermines the essence of free and fair elections. This economic influence not only distorts democratic values, but also leads to the election of individuals who may prioritize personal or business interests over public welfare. Overall, the research concludes that the impact of money in local elections is deep-rooted and complex. In the case of Chapainawabganj Sadar, it not only affects the fairness of electoral competition, but also raises serious questions about the quality of representation and accountability in local government. The study calls for stronger regulations, greater transparency, and civic awareness to ensure a more democratic and equitable electoral process at the local level.